1998
DOI: 10.1203/00006450-199809000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Major Vasodilator Role for Nitric Oxide in the Gastrointestinal Circulation of the Mid-Gestation Fetal Lamb

Abstract: As nitric oxide (NO) may be a particularly important vasodilator in early life, we investigated its role in the regulation of the gastrointestinal (GI) circulation at mid-gestation. Cardiac output and GI blood flow were measured by the radioactive microsphere technique in eight chronically instrumented and unanesthetized mid-gestation fetal sheep. Mean arterial pressure (MAP), heart rate, blood flow, oxygen delivery, and vascular resistance were determined before and after infusion of the specific NO synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…We found no differences in the response in PAP/SAP or in oxygenation index between preterm and term infants. This finding is in accordance with previous experimental studies: Even in the mid-gestational fetal lamb a specific NO inhibitor affects mean arterial pressure [9], and in the premature ovine pulmonary circulation, pulmonary vascular resistance is modulated by endogenous NO [10]. In clinical studies in preterm infants, NO improved oxygenation but did not improve survival [11,12].…”
Section: Discussionsupporting
confidence: 81%
“…We found no differences in the response in PAP/SAP or in oxygenation index between preterm and term infants. This finding is in accordance with previous experimental studies: Even in the mid-gestational fetal lamb a specific NO inhibitor affects mean arterial pressure [9], and in the premature ovine pulmonary circulation, pulmonary vascular resistance is modulated by endogenous NO [10]. In clinical studies in preterm infants, NO improved oxygenation but did not improve survival [11,12].…”
Section: Discussionsupporting
confidence: 81%
“…However, the vasodilator NO pathways appear to be functional at this gestation ( Figure 2 ). Similarly, NO-dependent basal intestinal flow has been demonstrated in vivo in 92- to 100-d GA ovine fetuses (27). …”
Section: Discussionmentioning
confidence: 79%
“…Simultaneously, there is a decrease in basal NOS activity with no increase in eNOS protein. Infusion of LNA to fetal lambs results in approximately 40% decrease in small intestinal blood flow in late gestation lambs compared with approximately 57% decrease (by 73 ml/kg/min/100 g) in mid-gestation lambs also suggesting lower basal NOS activity at late gestation (27,28). This late-preterm GA is associated with the highest imbalance between mediators of constriction and relaxation favoring the former.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2). NO exerts a range of functions in the gastrointestinal tract, acting as a pro-inflammatory stimulus, stimulating mucus secretion, opening chloride channels in the colon and promoting vasodilation (Brown et al 1992; Tamai and Gaginella 1993; Fan et al 1998). In addition, other authors have shown that citrulline alone induces endothelial relaxation as it enhances the production of NO, probably due to its recycling into arginine (Raghavan and Dikshit 2001).…”
Section: Resultsmentioning
confidence: 99%